Archbishop to honor Lynch (Raton Range Raton, New Mexico, 1982)
Newspaper Article on Monsignor Thomas J. Lynch's retirement.
Master list item #: 5
File location is in the Raton File Cabinet
Keywords: Sanchez, Robert; Lynch, Thomas J; Brasher, John; Lynch, William B; Marren, Mary; St. Patricks Church; St. Patrick's Parish; Raton Catholic School; Sacred Heart Parish; Our lady of Sorrows; St. Joseph's; Sacred Heart; St. Francis Xavier; Local History; Biography; Life and Customs; Religion; Catholic; Archbishop; Retirement; Priest; Raton, New Mexico; Santa Fe, New Mexico; Chicago, Illinois; Albuquerque, New Mexico; Las Vegas, New Mexico; Anton Chico, New Mexico; Costilla, New Mexico; Clayton, New Mexico